PEDOMAN HIDUP ISLAM DALAM KEHIDUPAN IPTEK DAN LINGKUNGAN - M. Fadli mubarak; Nur Izza; Dahlan Lama Bawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of science and technology (IPTEK) in the modern era has had a significant impact on human life, both positive and negative. The advancement of IPTEK is often accompanied by moral decline, spiritual crisis, and environmental damage. This article aims to analyze the Islamic Life Guidelines for Muhammadiyah Members (PHIWM) as a normative and ethical framework in responding to the development of IPTEK and environmental management. This research uses a qualitative-descriptive approach with a literature study method from official Muhammadiyah documents, the Qur'an, hadith, and relevant scientific literature. The results show that PHIWM positions IPTEK as a strategic tool for community welfare that must be developed responsibly, based on faith and morals. In addition, environmental management is seen as a theological mandate that demands a conservative, just, and sustainable attitude. Thus, PHIWM plays a crucial role in building integration between the advancement of IPTEK, individual piety, and environmental sustainability towards the realization of a truly Islamic society.